Sensitivities of seven algal species to triclosan, fluoxetine and their mixtures. Issue 1 (December 2018) - Bi, Ran; Zeng, Xiangfeng; Mu, Lei; Hou, Liping; Liu, Wenhua; Li, Ping; Chen, Hongxing; Li, Dan; Bouchez, Agnes; Tang, Jiaxi; Xie, Lingtian
Abstract Increasing release of pharmaceuticals and personal care products (PPCPs) into aquatic ecosystems is a growing environmental concern. Triclosan and fluoxetine are two widely used PPCPs and frequently detected in aquatic ecosystems. In this study, the sensitivities of 7 algal species from 4 genera to triclosan, fluoxetine and their mixture were evaluated. The results showed that the inhibitory effect on algal growth (EC50 -96h) of triclosan varied with 50 times differences among the 7 algal species.Chlorella ellipsoidea was the least susceptible species andDunaliella parva was the most sensitive species to triclosan. The inhibitory effect of fluoxetine was less variable than triclosan. Slightly higher toxicity of fluoxetine than triclosan was shown in the 7 tested algal species. No consistent pattern of the effects from mixture of triclosan and fluoxetine was observed among the 7 algal species and among the 4 genera. Additive effects of the mixture occured in 4 species and antagonistic effects in the other 3 species but no synergistic effect was detected. The algal species might show some sign of phylogenetic response to triclosan, as evidenced by the wide range of differences in their sensitivity at the genus level. This study provides important data which could be beneficial for biomonitoring programs on the ecological risk (algal species diversity) of these two chemicals.